Imaging of Paranasal Sinus Infections in Children: A Review. Issue 5 (30th May 2020) - Orman, Gunes; Kralik, Stephen F.; Desai, Nilesh; Meoded, Avner; Vallejo, Jesus G.; Huisman, Thierry A. G. M.; Tran, Brandon H.
ABSTRACT: Paranasal sinuses (PNS) infections are common in children. They may cause common and well‐known complications, but also, unusual and potentially devastating complications. Diagnosing PNS infections and complications in children requires knowledge of the unique anatomy of the nasal cavity and the PNS. In fetal life, nasal mucosa evaginations into the lateral nasal walls initiate the development of the PNS. The PNS continue to develop after birth and complete their maturation and pneumatization at different ages during childhood which makes the pattern of PNS infections determined by patient age. Complications are caused by direct spread of the infection to the orbit, face, intracranial or osseous structures or hematogenous spread of the infection to the intracranial structures. Emergent imaging studies are often necessary in the evaluation of the complications in pediatric patients when the symptoms persist for 10 days and/or if there is evidence of intracranial or orbital complications. In addition, immunocompromised children are especially vulnerable to developing unusual complications. Computed tomography (CT) is excellent for determining whether there is intraorbital extension of PNS disease. However, when the infection approaches the orbital apex, a magnetic resonance imaging (MRI) study with contrast is necessary to assess spread into the cavernous sinus and the intracranial compartment. The goal of this manuscript is to review and characterize imaging findings of PNS infections using CT and MRI allowing determination of the extent of PNS infections and their common and unusual complications in children. In addition, a summary of the development of the normal PNS is provided.